1997
DOI: 10.1142/s0218495897000168
|View full text |Cite
|
Sign up to set email alerts
|

Triggers and Barriers Affecting Entrepreneurial Intentionality: The Case of Western Australian Nascente Entrepreneurs

Abstract: This paper sheds light on the process leading to new enterprise formation while identifying the triggers and barriers to business start-ups. A new approach was used in this study to focus on the pre-decision stage, i.e. the intention and characteristics of nascent entrepreneurs. In addition to the "usual" triggers to start-up, this study has highlighted a more intriguing one: the will to invest savings in a business venture which will provide the investor with a job and the satisfaction of being rewarded on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 26 publications
2
27
0
2
Order By: Relevance
“…For example, Choo and Wong (2006) explored barriers perceived by 145 mid-career individuals in Singapore and found five major groups of barriers based on a pre-defined list: lack of capital, lack of skills, high risk, lack of confidence and compliant costs. These findings are consistent with several other studies reporting that a lack of financial resources were a major inhibiting factor to business start-up (Robertson et al, 2003;Volery et al, 1997). Further, in their recent work, Smith and Beasley (2011) investigated factors that influenced seven graduate students in the creative and digital industries to start their own businesses in the United Kingdom.…”
Section: Entrepreneurial Barrierssupporting
confidence: 87%
“…For example, Choo and Wong (2006) explored barriers perceived by 145 mid-career individuals in Singapore and found five major groups of barriers based on a pre-defined list: lack of capital, lack of skills, high risk, lack of confidence and compliant costs. These findings are consistent with several other studies reporting that a lack of financial resources were a major inhibiting factor to business start-up (Robertson et al, 2003;Volery et al, 1997). Further, in their recent work, Smith and Beasley (2011) investigated factors that influenced seven graduate students in the creative and digital industries to start their own businesses in the United Kingdom.…”
Section: Entrepreneurial Barrierssupporting
confidence: 87%
“…Access to finance is also the most widely recognised object of entrepreneurship policy, and insufficient finance is regularly cited by non-entrepreneurs as a barrier to starting a business (Volery et al, 1997;Kouriloff, 2000;Robertson et al, 2003;Choo and Wong, 2006). There is some evidence that restricted competition in banking and government credit controls can restrict entry in the non-financial sector (Cetorelli and Strahan, 2006;Kawai and Urata, 2002).…”
Section: Financementioning
confidence: 99%
“…Regulations constitute one of the most widely studied external conditions for business and entrepreneurial activity, and regulatory issues are cited regularly in studies of barriers to start-ups that are based on surveys of non-entrepreneurs (Grilo and Irigoyen, 2006;van Stel et al, 2007). Some studies have found that regulations, taxes and labour market rigidities tend to load together in analyses of barriers to start-up (Volery et al, 1997;Choo and Wong, 2006;Klapper et al, 2006;Acs, Desai and Klap-per, this issue).…”
Section: Government Regulationsmentioning
confidence: 99%
“…Later, Kuratko and Hodgetts (1995) and then Stewart et al (2003) also concluded "need for achievement" and "getting larger opportunities" were important entrepreneurial motivations. Bird (1989) and Volery et al (1997) also found intrinsic rewards such as to be one's own boss, control one's own future, satisfy the need for achievement, and to have control to be important entrepreneurial motivations. Similar findings were reported by Benzing et al (2005) in that "to be my own boss" and "to increase my income" are the two most important motivations for establishing a new venture; their findings also included the desire for gaining independence, for creating jobs, and for receiving public recognition.…”
Section: Entrepreneurial Motivationsmentioning
confidence: 99%